Nf1 Haploinsufficiency Alters Myeloid Lineage Commitment and Function, Leading to Deranged Skeletal Homeostasis. (21st May 2015) - Rhodes, Steven D; Yang, Hao; Dong, Ruizhi; Menon, Keshav; He, Yongzheng; Li, Zhaomin; Chen, Shi; Staser, Karl W; Jiang, Li; Wu, Xiaohua; Yang, Xianlin; Peng, Xianghong; et al.
ABSTRACT Although nullizygous loss of NF1 leads to myeloid malignancies, haploinsufficient loss of NF1 (Nf1) has been shown to contribute to osteopenia and osteoporosis which occurs in approximately 50% of neurofibromatosis type 1 (NF1) patients. Bone marrow mononuclear cells of haploinsufficient NF1 patients and Nf1+/– mice exhibit increased osteoclastogenesis and accelerated bone turnover; however, the culprit hematopoietic lineages responsible for perpetuating these osteolytic manifestations have yet to be elucidated. Here we demonstrate that conditional inactivation of a single Nf1 allele within the myeloid progenitor cell population (Nf1‐LysM) is necessary and sufficient to promote multiple osteoclast gains‐in‐function, resulting in enhanced osteoclastogenesis and accelerated osteoclast bone lytic activity in response to proresorptive challenge in vivo. Surprisingly, mice conditionally Nf1 heterozygous in mature, terminally differentiated osteoclasts (Nf1‐Ctsk) do not exhibit any of these skeletal phenotypes, indicating a critical requirement for Nf1 haploinsufficiency at a more primitive/progenitor stage of myeloid development in perpetuating osteolytic activity. We further identified p21Ras‐dependent hyperphosphorylation of Pu.1 within the nucleus of Nf1 haploinsufficient myelomonocytic osteoclast precursors, providing a novel therapeutic target for the potential treatment of NF1 associated osteolytic manifestations. © 2015 American Society for Bone and Mineral Research